Effect of Temperature on Drying Performance of Stingless Bee Pot-Pollen Using Swirling Fluidized Bed Dryer - Luqman, Abdul Halim; Firdaus, Basrawi; Mohammad Wajdi, Ibrahim; Ahmmad Shukrie, Md Yudin; Nurul Aini, Mohd Azman (2022)
Stingless bees or also called “Kelulut” in Malaysia are commonly known for its honey. Besides honey, pollen from flowering plants is also collected by worker bees, mixed with nectar and bee enzymes before storage cerumen pots in their hives. This bee product is called bee bread or pot. Pot-pollen is difficult to store owing to its high moisture content. This encourages microbes and fungi growth which will lead to spoilage. Thus, suitable drying method is required to preserve the pot-pollen for consumption. Swirling fluidized bed dryer is a promising method for drying pot-pollen. Usually, drying performance is dictated mainly by temperature. However, the significance of temperature on drying performance of stingless bee pot-pollen particularly using a swirling fluidized bed dryer has not been explored previously. Hence, the objective of this paper is to study the effect of temperature on the drying performance of stingless bee pot-pollen in a swirling fluidized bed dryer. Drying experiment is carried out a lab scale swirling fluidized bed dryer as shown in Figure 1. Pot-pollen sample with weight of 50 g is inserted into the drying chamber of a lab-scale swirling fluidized bed dryer with 67° swirling distributor, and the sample weight is taken every 5 minutes. The temperature tested is at 30 °C and 40 °C while the velocity is set at 1.5 m/s and 2.0 m/s. The results shown that, increasing temperature will lead to faster drying at all velocities tested especially at the earlier stages of drying. The air velocity increase will also lead to higher drying rates. However, the effect of velocity is diminished at higher temperature, indicating temperature being more significant parameter. On the other hand, the temperature increase should be minimal to prevent deterioration of pot-pollen composition. Thus, it can be concluded that temperature has a positive effect on the drying performance of stingless bee pot-pollen in a swirling fluidized bed dryer. Hence, a swirling fluidized bed dryer is proposed as a rapid drying method of stingless bee pot-pollen.